2010
DOI: 10.1371/journal.pone.0015858
|View full text |Cite
|
Sign up to set email alerts
|

Large Asymmetric Hypertrophy of Rectus Abdominis Muscle in Professional Tennis Players

Abstract: PurposeTo determine the volume and degree of asymmetry of the musculus rectus abdominis (RA) in professional tennis players.MethodsThe volume of the RA was determined using magnetic resonance imaging (MRI) in 8 professional male tennis players and 6 non-active male control subjects.ResultsTennis players had 58% greater RA volume than controls (P = 0.01), due to hypertrophy of both the dominant (34% greater volume, P = 0.02) and non-dominant (82% greater volume, P = 0.01) sides, after accounting for age, the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 36 publications
6
67
0
4
Order By: Relevance
“…This result is in line with previous conclusions Sanchis-Moysi et al, 2010a, 2010cYamada et al). Brosseau et al conclude that in side-to-side comparisons the dominant arm lean mass was 6-8 % greater than the non-dominant arm.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is in line with previous conclusions Sanchis-Moysi et al, 2010a, 2010cYamada et al). Brosseau et al conclude that in side-to-side comparisons the dominant arm lean mass was 6-8 % greater than the non-dominant arm.…”
Section: Discussionsupporting
confidence: 92%
“…Yamada et al, conclude that tennis players in particular have a remarkably greater ratio of dominant as compared to non-dominant lean mass in the upper arms (12.54±5.88 %) and forearms (10.38±4.35 %). Sanchis-Moysi et al (2010a, 2010c found in two studies that inter-arm asymmetry in lean mass is even higher and amounts to 12-15 %, which is connected with an increase of muscle volume in the dominant arm compared to the nondominant arm as a result of hypertrophy of loaded muscle groups (deltoid, triceps brachii, arm flexors and forearm superficial flexor muscles) during the execution of tennis strokes. This is particularly the case with all forehand shots and with serving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tennis and soccer induce the asymmetric hypertrophy of several trunk and leg muscles (Masuda et al, 2003;Sanchis-Moysi et al, 2010Idoate et al, 2011). The muscles of the lateral abdominal wall (OT: external oblique, internal oblique, and transversus abdominis) and quadratus lumborum (QL) play an important role during kicking and tennis strokes (Raty et al, 1999;Chow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%